Fracture characteristics and logging identification of lacustrine limestone-shale reservoirs in Da′anzhai Member, Gongshanmiao Oilfield, Sichuan Basin - Feng Wu; Yingying Luo; Yuhan Li; Zongheng Yang; Hongqian Zhang; Jianfeng Liu; Xiangchao Shi (地质科技通报, 2022)
Lacustrine limestone and shale reservoirs are both developed in the Da′anzhai Member of Gongshanmiao Oilfield, Sichuan Basin. Whether fractures are developed or not is the key to the reservoirs in the Da'anzhai Member. Based on core observations, CT scanning and scanning electron microscopy, the characteristics of fractures in limestone and shale were analyzed, the influences of sedimentary facies, mineral content, TOC and faults on fractures were analyzed, and identification plots of fractures in lacustrine limestone and shale were established. The results show that lacustrine limestone is mainly developed with structural fractures and interlayer fractures, while lacustrine shale is mainly developed with interlayer fractures, which are mainly horizontal and low-angle fractures. In the lacustrine limestone, the fractures are mainly developed in the thick limestone, thick limestone with asingle thin shale band and thick limestone with multiple thin shale bands in the Dasan Member and Dayi Member. In lacustrine shale, fractures are mainly developed in the interbeddedthin shale and thin limestone in theDaer-a Member. The ΔGR~ΔlogRT cross plot was preferred for lacustrine limestone fracture identification. Fractures in lacustrine shale were identified by the phenomena of increasing acoustic values and "negative difference" in dual lateral logging. The results can provide ideas and references for fracture evaluation of lacustrine limestone and shale.